Analysis of effect of promotion and word of mouth on purchase decision: Case of student University of Muhammadiyah Sumatera Utara - Mutia Arda (Proceedings of AICS - Social Sciences, 2017)
Muhammadiyah University of North Sumatra is one of the educational institutions in Muhammadiyah association. Marketing activities affect buyers' decisions to use services when they need them. Purchasing decisions are essentially related to "why" and "how" consumers' behavior. To attract prospective students choose services offered then it takes the promotion and word of mouth. The purpose of this study to test and analyze the influence of promotion and word of mouth on purchasing decisions UMSU students. The type of this research is descriptive quantitative and the nature of research using descriptive explanatory. The sample technique used in this study is the quota sampling of 100 respondents. Data analysis using multiple linear regression analysis. The results showed that promotion and word of mouth partially and simultaneously have a positive and significant influence on purchasing decisions UMSU students. But WOM has a more dominant influence on purchasing decisions of UMSU students compared to promotion.